Metabolic flexibility determines human NK cell functional fate in the tumor microenvironment - Poznanski, Sophie M.; Singh, Kanwaldeep; Ritchie, Tyrah M.; Aguiar, Jennifer A.; Fan, Isabella Y.; Portillo, Ana L.; Rojas, Eduardo A.; Vahedi, Fatemeh; El-Sayes, Abdullah; Xing, Sansi; Butcher, Martin; Lu, Yu; et al. (Cell metabolism, 2021)
NK cells are central to anti-tumor immunity and recently showed efficacy for treating hematologic malignancies. However, their dysfunction in the hostile tumor microenvironment remains a pivotal barrier for cancer immunotherapies against solid tumors. Using cancer patient samples and proteomics, we found that human NK cell dysfunction in the tumor microenvironment is due to suppression of glucose metabolism via lipid peroxidation-associated oxidative stress. Activation of the Nrf2 antioxidant pathway restored NK cell metabolism and function and resulted in greater anti-tumor activity in vivo. Strikingly, expanded NK cells reprogrammed with complete metabolic substrate flexibility not only sustained metabolic fitness but paradoxically augmented their tumor killing in the tumor microenvironment and in response to nutrient deprivation. Our results uncover that metabolic flexibility enables a cytotoxic immune cell to exploit the metabolic hostility of tumors for their advantage, addressing a critical hurdle for cancer immunotherapy.